Aggression Depicted in Suzanne Collins’ The Hunger Games - NANING CHOIRUN NISA (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
Aggression Depicted in Suzanne Collins’ The Hunger Games NaningChoirunNisa English Department, Faculty of Languages and Arts, State University of Surabaya Naningc5@gmail.com Prof. Dr. FD Kurnia, M.Pd. English Department, Faculty of Languages and Arts, State University of Surabaya Abstrak Studiinimembahastentangagresi yang dilakukanolehparapesertaThe Hunger Games, merekaadalahKatniss, Peeta, Cato, Clove, Glimmer, dan Thresh. Agresitelahmenjaditopikutamadidalam novel yang diterbitkantahun 2008 ini.Olehkarenaitu, studiinimembahasduapermasalahan, yakni (1) bagaimanaagresidigambarkan di The Hunger Gameskarya Suzanne Collins, dan (2) mengapaagresiterjadisebagaimanasepertiyang digambarkan di The Hunger Games karyaSuzanne Collins. Data daristudiinidiambildari novel sebagaisumberutamadanjugamembacasecaraintensifsebagailangkahselanjutnyauntukanalisis.Studiinimenggunakankonsepagresidaribeberapaahlidankonsepdeath instinctdari Sigmund Freud.Untukmenyelesaikanrumusanmasalahpertama, studiinimenggunakankonsepagresiuntukmendiskripsikanbagaimanaagresidilakukanolehparapeserta di dalamThe Hunger Games.Kemudianrumusanmasalahkeduadiselesaikanmenggunakanpendekatanpsikologiyakniteorideath instinctdanjugakonsepagresidari Anderson & Bushman untukmengungkapkanfaktorsituasidibaliktindakanagresiparapeserta.Terlebihlagi, penulismenggunakanpendekatanperpustakaan, analisis, danpenggambaran.Pendekatanperpustakaandigunakanuntukmencari datayang kemudiandianalisisberdasarkanteori yang ada.Penggambarandigunakanuntukmenjelaskanhasildarianalisis.Setelahmelaluianalisis yang panjangdenganmenggunakantigametodetersebut, makadapatdigambarkandenganjelasagresi yang dilakukanolehparapeserta, yakniKatniss, Clove, Cato, Peeta, Glimmer, dan Thresh.Hampirsemuatindakanagresimerekadipengaruhiolehdeath instinct, tindakanyang mengarahkepembinasahan, dantindakanagresikarenafaktorsituasi, sepertiisyaratagresi, provokasi, frustrasi, perasaansakitdantidaknyaman, obat-obatan, sertadorongan. Kata kunci :Agresi; kekerasan; death instinct; danfaktorsituasi. Abstract This paper deals with aggression done by the tributes of the hunger games, they are Katniss, Peeta, Cato, Clove, Glimmer, and Thresh. Aggression has become the main topic of this novel since it was published in 2008. Thus this study focuses on two major problems, (1) how is aggression depicted in Suzanne Collins’ The Hunger Games, and (2) why is aggression happened as depicted in Suzanne Collins’ The Hunger Games. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. The concept that will be used includes the concept of aggression by several experts and death instinct by Sigmund Freud. To answer the first problem, this study is using the concept of aggression to depict the aggression that is done by the tributes in the hunger games. Then the second problem is answered by using psychological approach of death instinct theory and the concept of aggression by Anderson & Bushman to reveal the situational factors behind their aggressions. Moreover, the writer used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it can reveal the depiction of aggression that is done by the tributes, Katniss, Clove, Cato, Peeta, Glimmer, and Thresh and most of their factors to do aggression is following their death instinct to destruction and aggression because of the situational factors, such as aggressive cues, provocation, frustration, pain and discomfort, drugs, and incentives. Keywords: aggression; violence; death instinct; and situational factors. INTRODUCTION: One of the main concern that has been increased nowadays is the issue of violence. Violence must be close related with aggression. As the World Health Organisation (1996) defines violence as an action that used the intentional of physical power, threatened or actual, against oneself, another person, or against a group or comunity that has results of harm. Anderson et al. (2002:29) state that violence is aggression whose goal is serious and extreme harm, i.e. death. All violence can be defined as aggression. However aggression is not always violent,i.e., a dentist intentionally gives a patient a shot of Novocain (it might be hurt), but the goal is to help rather than hurt the patient. In social psychology, the term of aggression is generally defined as any behavior that is intended to harm others who does not want to be harmed. Aggression is an external behavior that can be seen. i.e., a person shoots, hits, slaps, or threats someone. Aggression is a social behavior. It involves at least two people. In addition, aggression is intended to hurt, it is not happened accidental. Hence, an extreme and serious aggression may lead to violence. Aggression on violence has been a serious problem over the past decades. It can take several forms; physical aggression, verbal aggression, and relational aggression. Moeller (2001:25) defines physical aggression as actual physical activities that is intentionally intended to harm another person, animal, or object. i.e., hitting, pinching, hair-pulling, arm-twisting, strangling, burning, stabbing, punching, pushing, slapping, beating, shoving, kicking, choking, biting, force-feeding, threats with a weapon or object, any other rough treatment, or even murder.Verbal aggression involves the use of words to harm another persons,i.e.,teasing andthreatening (Moeller, 2001:25). Crick et al. cited in Moeller (2001:25) define relational aggression as “behaviors that harm others through damage (or the threat of damage) to relationships or feelings of acceptance, friendship, or group inclusion”. Whereas relational aggression, Crick &Grotpeter (1995) state that it is a behavior that is intended to hurt someone by harming their relationships with others. Furthermore, aggression on violence has portrayed in literature, i.e., in the novel. Novel deals imaginatively with human experience. Novel is a genre of fiction, and fiction may be defined as the art through the written word, representations of human life that instruct or divert or both(http://global.britannica.com/EBchecked/topic/421071/novel). One of the American author deals with the theme of aggression and violence in its works is Suzanne Collins. She is the author of several novels for younger readers. Collins, a 48-year-old mother of two children, began her writing career in television. Collins spent the 1990s writing kids’ shows for Nickelodeon, including Clarissa Explains It All (1993) and The Mystery Files of Shelby Woo (1997-98). She has also written for pre-school viewers on programs like Little Bear (1995-2003) and Oswald (2001-2008). Few other famous works of Collins includes her book Fire Proof: Shelby Woo (1999). When Charlie McButton Lost Power (2005) and When Charlie McButton Gained Power (2009). Then Collins switched to writing novels for young readers, and between 2003 until 2007 published five novels in The Underland Chronicles series: Gregor the Overlander (2003); Gregor and the Prophecy of Bane (2004); Gregor and the Curse of the Warmbloods (2005); Gregor and the Marks of Secret (2006); and Gregor and the Code of Claw (2007). In the same way, between 2008 until 2010 she published the other Series under the name The Hunger Games trilogy. These three books were The Hunger Games (2008); Catching Fire (2009); and Mockingjay (2010). Overall the series of The Hunger Games has been a great success, they are sold in more than 50 million print and electronic copies. The Hunger Games book has made a film version released in 2012 and for the second book Catching Fire in 2013. In addition, TheHunger Games novels have made Collins extremely popular amongst readers, and led her to be named one of Time Magazine’s Top 100 people in 2010, The New York Times Bestseller, 2009-10; Publishers Weekly Best Book of the Year, 2008; American Library Association (ALA) Best Book for Young Adults, 2009; and others. The Hunger Games has spent more than 260 consecutive weeks or more than five consecutive years to date on The New York Times bestseller list since publication in September 2008, and has also appeared consistently on USA Today and Publishers Weekly bestseller lists. It has been sold into 56 territories in 51 languages. However, some critics still appreciate the novel. “I was so obsessed with this book … The Hunger Games is amazing.” --- Stephanie Meyer. (http://www.thehungergames.co.uk/press_and_reviews) Hence this paper will discuss aggression in the hunger games based on Suzanne Collins’ first trilogy The Hunger Games where she reveals an outsize imagination for suffering and brutality in the post-apocalyptic nation of Panem, formerly known as North America. In Panem, the hunger games are an annual game which one boy and one girl between the ages of 12 to 18 years from their respective districts around the Capitol compete in a deadly battle until only one winner remaining. The winner will be famous and given prosperous life. The Hunger Games much presents on aggression that leads to violence. As Dewall et al. (2011:2) argue that violence is any aggressive behavior which is aimed to make harm physicaly, such as injury or death. Hence, theory of death instinct (thanatos) by Sigmund Freud and concept of aggression by Anderson & Bushman have developed to explain the reason of the tributes (Katniss, Peeta, Cato, Clove, Glimmer, and Thresh) doing aggression and violence acts. Thus, this study will discuss deeper aboutwhy people develop behaviors intended to hurt others as seen in The Hunger Games. Theoritical Framework Toassistandstrengthenthe datatobe analyzed, it willusea concept of aggression by several experts. To analyze the reasons that influence aggression, it will be explained frompsychological perspective (death instinct) by Sigmund Freud adds with concept of aggression by Anderson & Bushman. Based on the background of the study above, the questions below will be answered. How is aggression depicted in Suzanne Collins’ The Hunger Games? Why does aggression happen as depicted in Suzanne Collins’ The Hunger Games? Data Collection The data collection is taken from the novel The Hunger Games including the quotations, phrases, dialogues, or monologues in which reveal thought, speech, action, and attitude that reflects the idea of aggression. Limitation of the Study This study is limited and focused on aggression as depictedin Suzanne Collins’ The Hunger Games.The subject of this aggression is the tributes of The Hunger Games. They are KatnissEverdeen, Peeta, Cato, Clove, Glimmer, and Thresh. Thus, the focus on this study is the tributes of the hunger games who have done much aggression to hurt and harm others. The actions of the tributes of The Hunger Games in form of quotations, phrase, dialogues, or monologues in the novel that reveal as aggression, are taken as the data. Procedure of Analysis There were some steps taken in conducting this study. The first step is close reading of the novel to determine the major issue of it. The major issues are collected and proposed into a topic of the study by seeing the conflict, the monologue, the dialogue in the novel. After the topic is already decided, it is tried to figure out what should be analyzed with the topic. Thus it is collected two statements of problems. They are the depiction of aggressionand the factors that influence aggression in The Hunger Games. The next step is searching related information about concept of the topic and to figure it out, it is used a concept of aggression and a theory of death instinct (thanatos) by Sigmund Freud adding with concept of aggression by Anderson & Bushman. The synchronization of analysis and related concept was arranged to get the conclusion. RESULT Concept of Aggression In essence, aggression is an action that harms person or object (Moeller, 2001:2). Bartol cited in Moeller (2001:24) defines aggression as behaviors intended intentionally to harm another person physically or psychologically or to destroy or to take that person’s property. In additional, The Collins Concise Dictionary also defines aggression as “an attack, a harmful action, an offensive activity, a hostile, or destructive mental attitude.” (Harding, 2006:3). Aggression can start from the “low-level” acts, such as being impolite, making minor threats, and violating minor rules that are generally annoying acts. (Moeller 2001:22) Bartol et al. cited in Moeller (2001:25) state that aggression can also be hostile, instrumental, or reactive. Hostilehas the main purpose to harm or suffer the victim.Hostile aggression is driven byarousal, impulsivity, and immediate to situationalprovocation. It may be closer to the kinds of aggressionidentified by instinct theories. It includes irritableaggression.Instrumental aggression refers to unprovoked aggression used more force to get nonaggressive actions from the victim. Instrumental aggression is a learned response where aggression is a mechanism forachieving certain goals.In this mode aggression is just another way of gettingwhat you want or avoiding being criticised by authorityor gaining normal awards. i.e., a child beats another child to take some money (Bartol et al. cited in Moeller, 2001:25). In essence, instrumental aggression is not commonly followed by emotional feeling. It is just used as a way to get something else. Instrumental aggression involves defensive action, fight to get authority or want to dominate others.Whereas reactive aggression called as provoked aggression. It refers to an angry acts in response to some provokating environmental event or behaviors (Bartol et al. cited in Moeller, 2001:25). According to Pawlik et al. (2000:195) state that aggression that is used to survive depends on the individual organisms securing environmental resources. i.e., water as resources is freely available in humid country, so it does not need to fight to get it. The predatory species always hunt to get the food, on the contrary the prey (food) may resist themselves. Both predators and prey may engage in aggressive attack and defensive actions in this case. Furthermore, in his term of “intra-specific interactions”, Pawlik et al. explain that as individuals of the same species often have to compete for resources such as food or shelter. In one hand, in intra-specific antagonism aggression may occur in competition for social resources, i.e., mating partners or alienating. Characteristics of Aggression From some explanation of aggression above can be concluded the characteristics of aggression are: Aggression is aimed to hurt, to harm or to destroy others. Aggression is a release action of frustration, anger, or bad feeling. Types of Aggression Physical aggression Moeller (2001:25) defines phisical aggression as actual phisical activities that is intentionally intended to harm another person, animal, or object. i.e., hitting, pinching, hair-pulling, arm-twisting, strangling, burning, stabbing, punching, pushing, slapping, beating, shoving, kicking, choking, biting, force-feeding, threats with a weapon or object, any other rough treatment, or even murder. Verbal aggression Verbal aggression involves the use of words to harm another persons for such as teasing andthreatening. (Moeller, 2001:25) Verbal aggression includes acts such as insulting with bad language, displaying anger, threatening, swearing and being sarcastic all in order to cause emotional and psychological pain (Sameer &Jamia 2007), while National Youth Violence Prevention Research Centre (2002) state that verbal aggression includes such behaviors as threatening, intimidating others and engaging in malicious teasing and name-calling. (Onukwufor, J., 2013:64) Teasing is one of the type of verbal aggression. Teasing can be “playful” or “hurtful”. According to Dess, J. et al. (2011:2) state that teasing can be “playful” when; (1) teasing is used when we are talking with friends and everyone involves in the teasing, it is called as ‘teasing pie’, (2) teasing isn’t aimed to hurt, (3) teasing is done by closed friends, and (4) teasing is repeated again. However, teasing can be “hurtful” when; (1) teasing tends to direct into one person in a group, (2) teasing is sometimes repeated, (3) teasing is done by someone whom we do not recognize, (4) it is used to make fun of someone who having disability. Relational aggression Crick et al. cited in Moeller (2001:25) define relational aggression as “behaviors that harm others through damage (or the threat of damage) to relationships or feelings of acceptance, friendship, or group inclusion.” Crick &Grotpeter (1995) also agree that relational aggression is behavior that is intended to hurt someone by harming their relationships with others.(http://www.hopehouseonline.org/pages/gorls.shtml, 2010-2011) Little, Jones, Henrich, & Hawley cited in Young E. (2010:2) categorize relational aggression into two parts; reactive relational aggression and instrumental relational aggression. Reactive relational aggression is used to respond to provocation. People used this aggression by manipulating social issues, such as spreading rumors, as a response to feeling threatened or angry. Whereas instrumental relational aggression is “manipulating relationships or using aggression to get what one wants.” The Relationship between Aggression and Violence Anderson, C., &Huesmann, L. cited in Hogg & Cooper (2003:298) state that aggression is any behavior that is intended to harm directed toward others. Furthermore the agent of aggression will make sure that his aggression will harm the target. However, the target will automatically avoid the aggression as a defensive action. Anderson, C.A., & Bushman B.J. (2002:29) state that violence is aggression that has extreme harm as its goal, i.e., death. Tolan and Guerra cited in Moller (2001:2) state that violence is “the most extreme and serious” form of aggression. Anderson et al. (2002:29) state that all violence can be defined as aggression. However, in some cases of aggression are not always violent. i.e., a child is pushing his friend’s tricycle is an act of aggression but is not an act of violence. To reach that serious and extreme goal, such as injury or even death, must be expressed into visible way, i.e., physical aggression. Thus aggression can lead to violence if it is happened on physical aggression. Because the goal of aggression that leads to violence is to hurt and to harm the target of aggression. Moreover, Anderson, C., &Huesmann, L. cited in Hogg & Cooper (2003:298) also agree that “violence is physical aggression at the extremely high end of the aggression continuum, such as murder and aggravated assault.” Harding (2006:4) adds that aggression is the easiest to recognize in violence. She calls it as “the rawest manifestation being ‘destructive motor action’.” In addition, The World Health Organisation (1996) also defines violence as an action that used the intentional of physical power, threatened or actual, against oneself, another person, or against a group or comunity that has results of harm or even death. Hence, in social psychology, violence is aggression that has extreme physical harm as its goal, such as injury or death. One child intentionally pushing another child down is an act of aggression but it is not an act of violence. One person intentionally hitting, kicking, shooting, or stabbing another person is an act of violence. Thus, violence is a subset of aggression. All violent acts are aggressive, but not all aggressive acts are violent (only the ones that are intended to cause extreme physical damage are called violent). Factors Influencing Aggression Drives Drive derived from a German word Trieb which refers to a stimulus within person. This word is generally understood as instinct, inborn patterns of behavior that are biologically determined rather than learned with its characteristics that are both physical (bodily needs) and psychological (wishes). Drives operate as a constant motivational force. Freud proposed that drives consists of two parts; sex (eros) and aggression (thanatos). (Feist, 2008:31) Death Instinct Death Instinct is the concept made by a psychoanalist, Sigmund Freud. Thomas cited in Moeller (2001:26) states that Freud assumes that human born with a drive, called the Thanatos. To Allen (2006:24), thanatos is the instinct toward destructiveness and death which is aimed at returning living things to their original lifeless state. Freud stated in Li (2011:116) defines thanatos as “an urge inherent in organic life to restore an earlier state of things”. Thanatos might be directed toward the self that is resulting in self-injury or even death, it can be also directed toward others that is resulting in aggression. The instinct theory of aggression derives mainly from two sources: psychoanalysis and ethology. According to psychoanalytic theory, human behavior is motivated by two sets of opposing instincts: Eros, consisting of all those forces aimed at furthering life, and Thanatos, consisting of all those forces striving for the destruction of life (Freud, 1933). When Thanatos, the death instinct, is discharged outward, the result is aggressive behavior. If this instinctual drive is not expressed, it continues to build up within the individual until it is relieved either by an explosive act of violence or until it is turned inward as self-destructive behavior. Since the aggressive drive is constantly seeking an outlet, the theory is basically a pessimistic one in that aggression is seen as an unavoidable part of human behavior. Indeed, Montague (1968) has argued that instinct theory, in its emphasis on the hostile and destructive nature of humans, relates quite closely to the doctrine of the "innate depravity" of man, a doctrine which we have seen first gained ascendancy in medieval theological thought. (Goldstein, et al., 1981: 4) However, there are some ways to shift the strength of death instinct (thanatos). Those are through defense mechanism of sublimation, displacement, and chatarsis. (Moeller, 2001:26) Sublimation Thomas cited in Moeller (2001:26) defines sublimation as “a process by which unacceptable drives are channeled into socially acceptable alternatives.” i.e., children can drain or sublimate their aggressiveness drive toward positive activities, such as sports that trained physically. Displacement Feshbach cited in Moeller (2001:26) states that children tend to displace their aggressiveness drive toward other things. This is happened because they can not express their aggressiveness drive directly toward person that caused frustration. Catharsis Renfrew cited in Moeller (2001:26) states that in the discussion of aggression, Freud assumes that “if the strength of the aggressive drives begins to build up, something must be done to release the energy associated with the drive before it becomes too intense and overt aggression is discharged in its entire fury.” Level of Awareness In his theory of personality, Sigmund Freud categorizes human’s level of awareness into three types; conscious, preconscious, and unconscious. Freud stated in Feldman (2003:328) states that unconscious motivated much of our behaviors. He defines unconscious as “a part of the personality of which a person is not aware.” Whereas conscious is just the upper of our psychological. Some of our conscious is made by our preconscious, an action that is not threatening and be able to remember easily, i.e., 2 + 2 = 4. Hence, instinctual drives that Freud proposed into two parts, eros and thanatos, exist in unconscious. Eros and thanatos are hidden from conscious awareness because they will cause pain in our lives. To Freud, unconscious considered as “safe haven” of threatening events (Feldman, 2003:329). Id, Ego, and Super ego To describe the structure of personality, Freud develops three components of human psychic as Id, Ego, and Super ego. The id is the raw, unorganized, inborn part of personality. From the time of birth, the id attempts to reduce tension created by primitive drives related to hunger, sex, aggression, and irrational impulses. These drives are fueled by “psychic energy”, or libido as Freud called it. [...]. The ego strives to balance the desire of the id and the realities of the objective, outside world. [...]. The super ego, the final personality structure to develop, represents social right and wrong as taught and modeled by a person’s parents, teachers, and other significant individuals (Feldman, 2003:329). According to Brakel, et al. cited in Allen (2006:23-24) state that the id is the origin of personality. The Id is beyond conscious awareness. It operates based on the pleasure principle, which is aimed to reduce the tension and get the satisfaction of physical drives, involving sex and hunger, or primitive psychological needs, such as comfort and protection from danger. The Id satisfies its needs without consideration whereas it is right or wrong. Furthermore, Freud cited in Allen (2006:24) assumes that id is the place where instincts existed, which consists of instinct toward life, called Eros, and instinct toward destructiveness and death, called Thanatos. The Id is powered by libido, involves “physical desire”, “erotic tendencies”, “sexual desire in the broadest sense”, and “the motive forces of sexual life”. The ego works based on the reality principle. It prevents the fulfillment of the demand of the id until an appropriate object is found that will allow gratification without harmful side effects. The instinctual energy from the id will be controlled based on reality of the individual safety and the social factors. Allen (2006:24) defines the ego as “a coherent organization of mental process that develops out of the id energy, has access to consciousness, and is devoted to contacting reality for the purpose of satisfying id needs”. The ego operates through secondary process, i.e. thinking, evaluating, planning, and decision making. It plans for actions in the real world that will satisfy the id. However, the ego is not totally conscious. On both conscious and unconscious levels, the ego gets easily both external and internal dangers. External dangers involve insufficient food, water, and physical comfort as well as threats of physical or psychological injury and lose of parental love. Internal dangers involve uncontrollable increases of instinctual energies, particularly sex and aggression. In essence, the ego process increases the likelihood that the id will experience satisfaction of its effect without of harmful side effects. For the third personality structure, the super ego. Allen (2006:24) defines it as “the representation of society in personality that incorporates the norms and standards of the surrounding cultures.” The super ego works based on morality principle, a code that concerns society’s values regarding right and wrong. The super ego is divided into two parts; the conscience and the ego-ideal (Feldman, 2003:329). The conscience prevents us from behaving in a morally improper way by making us feel guilty if we do wrong, and the ego-ideal, which represents the “perfect person” that we wish we were, motivates us to do what is morally right (Feldman, 2003:329). Like the ego, the super ego develops from the id energy. The most important function of the super ego is to help control the id impulses by directing energy toward entirely inhibiting the id’s expression of its sexual, aggressive, and other antisocial instincts. In essence, the super ego, like the ego, addresses the id needs, but the super ego seeks to suppress those needs rather than satisfy them (Allen, 2006:26). Situational Factors 1. Aggressive Cues Aggressive cues related to objects that influencing on aggression. Berkowitz &LePage cited in Anderson & Bushman (2002:37) do the research on the angered participants and conclude that the presence of weapons such as gun can increase such aggressive behaviors. In additional, Anderson & Bushman state that aggressive cues exist in human memory. Thus the existence of weapons or any other things that can be used to harm can automatically prime aggressive thought that causing on aggression in reality. 2. Provocation Berkowitz &Geen cited in Anderson & Bushman (2002:37) state that interpersonal provocation is one of the factors that influencing on human aggression. Cowie et al. &Folger et al cited in Anderson & Bushman (2002:37) also argue that provocations involved unpleasant treatment such as any rough treatment of verbal aggression and physical aggression and one’s interfere to reach the goal. 3. Frustration According to Anderson & Bushman (2002:37) define that frustration is an obstacle to reach the goal. Most of the actions of provocation can be the type of frustration. Moreover, frustration will identify someone who causes its failure and it is succeed to increase the aggression against someone who is responsible of this frustration and even someone who is not responsible for this failure too.Moreover, frustration commonly happens related to hostile aggression and uncommon happens in instrumental aggression. 4. Pain and Discomfort Berkowitz cited in Anderson & Bushman (2002:38) states that any discomfort feeling or ‘non social aversive condition’, i.e., hot temperatures, noises, and unpleasant odors will increase aggression. Berkowitz et al. add that the worse unpleasant condition such as pain will also produce on aggression. 5. Drugs Bushman (1993) cited in Anderson & Bushman (2002:38) states that any kind of drugs and alcohol lead to aggression. This aggression tends to be indirect rather that direct. 6. Incentives According to Anderson & Bushman (2002:38) state that incentives almost has the same purpose with instrumental aggression. It is an urge to own someone’s things. More valuable the object, more people want to get it. Thus it produces on aggression. Role of Anger Anger is the causes of aggression. Anderson & Bushman (2002:44) propose into five roles of anger on aggression; (1) anger may give a justification of a revenge attack and anger may interfere with higher cognitive process, (2) anger allows person to defend their aggressive intention over time. In provoking situation, anger will increase the attention and the depth of it, (3) anger as information cue, (4) anger primes aggressive thoughts, scripts, and related with any expressive motor behaviors, (5) aggressive behavior has the main energy or source from anger feeling. DISCUSSION: Physical Aggression The first physical aggression in the novel is depicted by KatnissEverdeen, a tribute from district twelve, in the quotation below. It’s excellent shooting. I turn to the Game makers. A few are nodding approval, but the majority of them are fixated on a roast pig that has just arrived at their banquet table. Suddenly I am furious, that with my life on the line, they don’t even have the decency to pay attention to me. That I’m being upstaged by a dead pig. My heart starts to pound, I can feel my face burning. Without thinking, I pull an arrow from my quiver and send it straight at the Gamemakers’ table. I hear shouts of alarm as people stumble back. The arrow skewers the apple in the pig’s mouth and pins it to the wall behind it. Everyone stares at me in disbelief. (ch.7, pp.101-102) Physical aggression is the most visible violence. Physical aggression uses physical power intentionally to harm or destroy object or person. i.e.,hitting, pinching, hair-pulling, arm-twisting, strangling, burning, stabbing, punching, pushing, slapping, beating, shoving, kicking, choking, biting, force-feeding, threats with a weapon or object, any other rough treatment, or even murder. From the words ‘I pull an arrow from my quiver and send it straight at the Gamemakers’table’ clearly shows the depiction of physical aggression that is done by Katniss. Moeller (2001:2) argues that aggression is an action that harms a person or object. From the words ‘The arrow skewers the apple in the pig’s mouth and pins it to the wall behind it’ become the part that shows the purpose of aggression that is to harm or to destroy something. The object that is destroyed here is the apple that is in the pig’s mouth. Katniss does her aggression is supported by the presence of weapon, that are bow and arrows. This weapon smoothens her to attack the game makers who do not give attention to her talent. Moreover, the bow and the arrows have been existed in her hand at that time. So it is easy to her to use it. Even it happens beyond her awareness to use the arrows to attack the game makers. Her aggression is categorized into hostile aggression. Bartol et al. cited in Moeller (2001:25) state that Hostilehas the main purpose to harm or suffer the victim.Hostile aggression includes irritableaggression. Hence Katniss does the aggression is motivated by her anger feeling and her revenge because she is not given attention from the game makers. Without thinking any longer she shoots the apple in mouth of the dead pig on the table of the game makers. So all the game makers now give her full consideration. Verbal aggression “Forget it, District Twelve. We’re going to kill you. Just like we did your pathetic little ally . . . what was her name? The one who hopped around in the trees? Rue? Well, first Rue, then you, and then I think we’ll just let nature take care of Lover Boy. How does that sound?” Clove asks. “Now, where to start?” (ch.21, p.285) From the quotation above, the words ‘We’re going to kill you. Just like we did your pathetic little ally’ depict the threatening action that is done by Clove. She says that she wants to kill Katniss like she has done to Rue. Those words also explain the purpose of verbal aggression, sarcastic action that is done to cause emotional and psychological pain of the target. From the words ‘your pathetic little ally . . . what was her name? The one who hopped around in the trees? Rue?’ clearly depict that Clove has insulted Rue as a trifle tribute who is able to kill every time. She says so to make Katniss feels more furious and this will make Clove satisfies with her verbal aggression. As we know that the goal of verbal aggression is to harm the target by using words. Moreover, Clove also tries to make her target becomes fear of her. It is shown from the words ‘Forget it, District Twelve’. It means that she makes sure that Katniss will not be able to go home to her district again because she will die. The words ‘your pathetic little ally’ also said by Clove to tease Katniss. She calls Rue not by her name but she makes her own name –calling for Rue. It depicts the insulting action done by Clove. Moreover, she also teases Katniss by giving a name-calling to Peeta with ‘lover boy’. As the purpose of verbal aggression is to make the target furious and hurt psychologically. The words ‘Now, where to start?’Also depicts her teasing before she begins her aggression to Katniss. The point is she wants to make Katniss becomes fear with all her actions and it results on satisfy and pleasure to her. Psychological Factor Aggression is firstly depicted by KatnissEverdeen, a tribute from district twelve, in the training season of the hunger games. When she shows her talent in front of the game makers in an excellent shooting, unfortunately she does not get full attention from the game makers. This makes her becomes mad and do the aggression towards the game makers to express her anger feeling. It’s excellent shooting. I turn to the Game makers. A few are nodding approval, but the majority of them are fixated on a roast pig that has just arrived at their banquet table. Suddenly I am furious, that with my life on the line, they don’t even have the decency to pay attention to me. That I’m being upstaged by a dead pig. My heart starts to pound, I can feel my face burning. Without thinking, I pull an arrow from my quiver and send it straight at the Gamemakers’ table. I hear shouts of alarm as people stumble back. The arrow skewers the apple in the pig’s mouth and pins it to the wall behind it. Everyone stares at me in disbelief. “Thank you for your consideration,” I say. Then I give a slight bow and walk straight toward the exit without being dismissed. (ch.7, pp.101-102) From the psychological perspectives, Freud explains that human born with its death instinct that leads to destructiveness. From the words ‘Withoutthinking, I pull an arrow from my quiver and send it straight at the Gamemakers’ table’ clearly shows the purpose of the death instinct. The words ‘without thinking’, describes her unconscious that Freud said it is the major driving power of death instinct. From the words ‘Thank you for your consideration’, shows the id of hers. She has gotten attention from the game makers. It means this is her purpose to reach the satisfaction and pleasure. As Brakel, et al. cited in Allen (2006:23) states that the idoperates based on the pleasure principle. Hence the Id satisfies its needs without consideration whereas it is right or wrong. Situational Factor Aggression done by the tributes can be caused by the situational factors involving aggressive cues, provocation, frustration, pain and discomfort, drugs, and incentives. This concept of aggression is taken by the explanation of Anderson & Bushman (2002). Situational factors that influencing the aggression of the tributes is firstly depicted by KatnissEverdeen, a tribute from district twelve. She attacks the game makers because she does not get the attention from them and any other situational factors also can be influencing her indeed. It is shown in the quotation below: It’s excellent shooting. I turn to the Game makers. A few are nodding approval, but the majority of them are fixated on a roast pig that has just arrived at their banquet table. Suddenly I am furious, that with my life on the line, they don’t even have the decency to pay attention to me. That I’m being upstaged by a dead pig. My heart starts to pound, I can feel my face burning. Without thinking, I pull an arrow from my quiver and send it straight at the Gamemakers’ table. I hear shouts of alarm as people stumble back. The arrow skewers the apple in the pig’s mouth and pins it to the wall behind it. Everyone stares at me in disbelief. “Thank you for your consideration,” I say. Then I give a slight bow and walk straight toward the exit without being dismissed. (ch.7, pp.101-102) From the quotation above, there are several situational factors of causing violence that will be explained. The words ‘Suddenly I am furious, that with my life on the line, they don’t even have the decency to pay attention to me’ shows the anger feeling that becomes the reason of her to do the aggression. Anderson & Bushman (2002:44) said that anger allows person to defend their aggressive intention over time. It is shown from the words ‘I give a slight bow and walk straight toward the exit without being dismissed’. She still feels angry till go out without given a permission from them. It is because she has been furious being ignored by several game makers that should pay attention to her. From the words ‘That I’m being upstaged by a dead pig’ shows her revenge toward the game makers who have compare her with a dead pig until they all more attentive to a dead pig than to her. Thus this feeling influences her to do aggression as a retaliation. As Anderson & Bushman (2002:44) said that anger may give a justification of a revenge attack. Hence, they argue that aggressive behavior has the main energy or source from anger feeling. Moreover, ‘an arrow’ that is provided in the arena with game makers can also be one of the factor that influencing on her aggression. As Anderson & Bushman (2002:44) said that the arrows indicates on the aggressive cues. They explain that aggressive cues exist in human memory and its existence can automatically prime aggressive thought that causing on aggression in reality. CONCLUSION: Based on the analysis explained in the previous chapter, there are two main conclusions about aggression depicted by the tributes of The Hunger Games since in the training until in the arena is influenced by two factors: aggression because of death instinct and aggression because of the situational factor. Aggression done by the tributes is generally influenced by death instinct. Death instinct as behaviors intended intentionally to harm another person physically or psychologically or to destroy or to take that person’s property clearly depicted in the hunger games. Death instinct that has the main purpose of destruction may leads people to do aggression because of their pleasure. Death instinct might be directed toward the self that is resulting in self-injury or even death, it can be also directed toward others that is resulting in aggression. The tributes’ actions from physical aggression until verbal aggression show the purpose of the aggression that is harming others or objects.The tributes do the aggression beyond their conscious. The unconscious part supports their Id works. The Id operates based on pleasure principle. It will develop death instinct to hurt others or to destroy anything. Hence aggression is done to satisfy their desire. By expressing their destructive instinct, they can reach their pleasure and satisfaction. Aggression done by the tributes is also much influenced by the situational factors; aggressive cues, provocation, frustration, pain and discomfort, and incentives. First, the presence of weapon may lead the tributes to do aggression. The game makers of the hunger games provide the weapon supply for the tributes so that they can survive in the arena. It can be seen that the presence of weapon much influence them to be aggressive and attack others. On the other side, weapon can be used as a defensive action, however, they still tend to use violence to protect themselves from dangerous. Second, provocation may lead the tributes to do aggression. Provocation involves unpleasant treatment such as any rough treatment of verbal aggression and physical aggression and one’s interfere to reach the goal. The third is frustration. Frustration much influences the tributes to do the aggression. It happened if someone is blocked by something to reach its goal, need, want, and hope. The tributes do the aggression as a response toward their frustration. It commonly accompanied by a strong anger feeling. Fourth, Pain and discomfort may also influence the tributes of the hunger games to do the aggression. Pain commonly comes when someone feels discomfort and it urges them to do the aggression toward anything around them. Thus pain and discomfort become one of the factors influencing the tributes to do the aggression. The last is incentives. Incentives much influence the tributes to attack others, however, it is not aimed to hurt or destroy other physically or verbally. It generally does because of the desire to own the other’s thing. Thus they do the aggression to reach their goal. The last factor/reason that much influences the tributes to act aggressive in almost every single aggression is anger feeling. When they feel angry, they must have a feeling of aggressing, slamming, and destroying anything which reflected as bad behaviors, so they express it a response of anger feeling. Anger comes from any factors; hurt physically, humiliation, disappointment, threat, and other rough treatments. Those actions can prime an aggression happened. Furthermore, anger has five roles in its process; anger as a revenge attack, anger allows person to defend their aggressive intention over time, anger primes aggressive thoughts, scripts, and related with any expressive motor behaviors, and anger is the main energy or source for aggressive behavior. To sum up, the aggression done by the tributes lead to violence that has extreme physical harm as its goal, such as injury or even death. This happened only in physical aggression and their aggression is influenced by psychological and situational factors. References: Allen, B. (2006). Personality theorist: development, growth, and diversity (5thed). USA: Pearson education. Anderson, C.A., & Bushman B.J. (2002).Human aggression.Annual Reviews.Psychology. 2002.53:27-51. Downloaded from: arjournals.annualreviews.org by Purdue University Library on 02/08/05. Collins, Suzanne. (2009). The Hunger Games. Malaysia: Scholastic. Dess, J., et al. (2011). Understanding Playful vs. Hurtful teasing and Bullying Behavior. The prevention intervention center for cobb country school district. Available at: www.cobbk12.org/preventionintervention. Dewall, Anderson, & Bushman. (2011). The General Aggression Model: Theoretical Extensions to Violence. American Psychological Association. Vol. 1, No. 3, 245–258. Feist, J., &Feist, G. J. (2008).Theories of personality (7th Ed.). USA: McGraw-Hill. Feldman, Robert S. (2003). Essentials of Understanding Psychology (5th ed). New York: McGraw-Hill. Freiberg, Karen L (ed). (2001). Human development (9thed): why the young kill. USA: McGraw-Hill. Goldstein, et al., (1981).In Response to Aggression. USA: Pergamon. Harding, Celia (ed). (2006). Aggression and Destructiveness Psychoanalytic Perspectives.New York: Routledge. Hogg, M. & Cooper, J. (eds). (2003). The Sage Handbook of social Psychology.Thousand Oaks, CA: Sage Publications. 296-323. Jesmin, U.H. (2012). Eros and Thanatos in the Psychical Process of Paul Morel: Diversity in Paul’s Psyche.Journal of Literature and Art Studies, ISSN 2159-5836. Vol. 2, No. 5, 538-543 Li, Quixia. (2011). A study of Mrs. Dalloway from the perspective of Freud’s theory of Thanatos.Journal of Cambridge Studies. Vol. 6, No. 1, 115-123. Lochman, et al. Anger and Aggression.The University of Alabama, Tuscaloosa.115-134. Onukwufor, J. (2013). Physical and Verbal Aggression among Adolescent Secondary School Students in Rivers State of Nigeria.British Journal of Education.Vol.1, No.2, pp. 62-73. Pawlik, K., &Rosenzweig, M. (2000).The international handbook of psychology. Great Britain: Sage. Thomas G, Moeller. (2001). Youth Aggression and Violence : A Psychological Approach. Mahwah, NJ: Lawrence Erlbaum Associates. Young, E., et al. (2010). Relational Aggression in Schools: Information for Educators. East West Highway, Suite 402, Bethesda: National Association of School Psychologists. World Health Organization (WHO).(1996). WHO Global Consultation on Violence and Health. Violence: a public health. Geneva. (document WHO/EHA/SPI.POA.2). available at: http://www.who.int/violenceprevention/approach/definition/en/ Internet Source : http://www.guidetopsychology.com/ad_viol.htm, 1997-2013. http://global.britannica.com/EBchecked/topic/421071/novel, 2014. http://www.beyondintractability.org/essay/aggression, retrieved at July 2004. http://www.hopehouseonline.org/pages/gorls.shtml, 2010-2011. http://www.psyking.net/id183.htm, February 2004. http://www.psychologytoday.com/basics/embarrassment, 2002-2014. http://apa.org/topics/anger/index.aspx Suzanne Collins. (2014). The Biography.com website.Retrieved 12:30, Apr 08, 2014, from http://www.biography.com/people/suzanne-collins-20903551. http://www.thehungergames.co.uk/press_and_reviews